Handbook of behavioral economics : foundations and applications. - Bernheim, B. Douglas; Della Vigna, Stefano; Laibson, David I. (Handbooks in economics., 2018)
"Handbook of Behavioral Economics: Foundations and Applications presents the concepts and tools of behavioral economics. Its authors are all economists who share a belief that the objective of behavioral economics is to enrich, rather than to destroy or replace, standard economics. They provide authoritative perspectives on the value to economic inquiry of insights gained from psychology. Specific chapters in this first volume cover reference-dependent preferences, asset markets, household finance, corporate finance, public economics, industrial organization, and structural behavioural economics. This Handbook provides authoritative summaries by experts in respective subfields regarding where behavioral economics has been; what it has so far accomplished; and its promise for the future. This taking-stock is just what Behavioral Economics needs at this stage of its so-far successful career. Helps academic and non-academic economists understand recent, rapid changes in theoretical and empirical advances within behavioral economics. Designed for economists already convinced of the benefits of behavioral economics and mainstream economists who feel threatened by new developments in behavioral economics. Written for those who wish to become quickly acquainted with behavioral economics."--